Repentant Speeches: A Pragmatic Study through Speech Acts - Al-Rashidi, Amer Samar Mufleh Qaaboub (Arts for Linguistic & Literary Studies, 2024)
This research endeavors to explore repentant speeches through a pragmatic lens, focusing on speech acts to elucidate their meanings and intentions. Employing a pragmatic approach, particularly within the framework of speech act theory, the study comprises an introduction and preface discussing the historical and contextual background of repentant sermons, followed by two sections. The first section examines direct speech acts within repentant sermons, while the second delves into indirect speech acts. The research yields several noteworthy findings, notably that repentant sermons predominantly feature direct, directive speech acts, indicating a prevalence of direct verbal expressions. The efficacy of directness in conveying achievement is highlighted. Conversely, indirect speech acts wield significant influence on recipients by implying rather than explicitly stating, a strategy commonly employed by repentant speakers in their sermons.